Nuclear spectroscopy of iodine isotopes with A>134 - Achterberg, Erhard O. J.; De Aisenberg, E. Y.; Iglesias, F. C.; Jech, Alberto Estanislao; Moragues, Jaime Baudilio A.; Otero, D.; Pérez, M. L.; Proto-Otero, A. N.; Rossi, J. J.; Scheuer, W.; Suárez, J. F. (European Organization for Nuclear Research (CERN), 1970)
Fil: Achterberg, E. O. Comisión Nacional de Energía Atómica; Argentina